Transient degradation of NF-κB proteins in macrophages after interaction with mast cell granules - Noriko Ito; Yuai Li; Tsuneo Suzuki; Daniel J. Stechschulte; Kottarappat N. Dileepan (Mediators of Inflammation)
The exposure of the macrophage cell line, J774 to mast cell granules (MCG) led to the form ation of altered nuclear transcription factor proteins (NFκBx), which had faster electrophoretic mobility than the p50 homodimer of NF-κB, but retained comparable DNA binding capacity. Antibodies to N-terminal peptides of p50, p52, p65 or c-Rel supershifted only a fraction of NF-κBx. Western blot analyses revealed that nuclear p65 and c-Rel were progressively degraded after exposure to MCG, whereas nuclear p50 appeared to be unaffected. In contrast, cytoplasmic p50, p65, c-Rel as well as IkBα remained intact after MCG treatment, although p52 was clearly degraded. In comparison to J774 cells, incubation of m ouse peritoneal macrophages with MCG resulted in more extensive alterations to NF-κB proteins. The alterations in NF-κB proteins did not affect the expression of inducible nitric oxide synthase (iNOS) or TNF-α mRNA in J774 cells. These data indicate that exposure of J774 cells to MCG leads to generation of altered nuclear p52, p65 and c-Rel, which retain intact N-terminal peptides, specific oligonucleotide binding and transactivating activity. On the other hand, in peritoneal macrophages, MCG induce more extensive modifications to NF-κB proteins with associated inhibition of iNOS or TNF-α mRNA expression.